The Relationship of Self-Efficacy with Learning Discipline of Teenagers during COVID-19 Pandemic at East Kalimantan, Indonesia - Indah Kumala Sari; Yati Sri Hayati; Nurona Azizah; Alfrina Hany (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2021)
As a result of the COVID-19 pandemic, learning activities are now conducted at various levels using online methods, giving students more freedom to organize their learning activities. For this reason, students must be disciplined to complete their learning activities. One of the factors that play an important role in student learning discipline is seIf-efficacy. The purpose of this study was to determine the relationship between self-efficacy and teenagers' learning discipline during the COVlD-19 pandemic. This research design used correlational descriptive with the cross-sectional approach. The research sample amounted to 254 respondents who were taken with stratified random sampling technique. Data were collected through questionnaires to measure teenagers’ self-efficacy and learning discipline during the COVID-19 pandemic. Data were analyzed using the Spearman rank test. The results showed that self-efficacy of teenagers was in the high category as much as 81.5%, and learning discipline during the COVID-19 pandemic was in a good category as much as 42.9%. The findings showed that the significance value was 0.000 (α = 0.05) and the correlation coefficient was 0.309. So we can conclude that there is a significant relationship between teenagers' seIf-efficacy and Learning discipline during the COVlD-19 pandemic. It is expected that nurses and teachers will counsel students and supervise learning activities to ensure that students maintain their learning discipline.